Influence Of Infant Massage On Increase In Baby Weight In Infants Aged 2-6 Months At The Midwife Clinic Halimah Lubis Districts Deli Serdang Year 2022 - Siti Embun Hasibuan; Basaria Manurung; Maria Ulfah; Rani Sari; Sutra Warni (Institute of Computer Science (IOCS), 2022)
Baby massage is a form of touch therapy that is very beneficial for both babies and their parents. Touch or massage on babies can stimulate milk production, increase appetite and weight. This action will also strengthen the bond of love between parents and children, and become a positive basis for the emotional and physical growth of the baby. This study aims to determine the effect of infant massage on increasing infant weight in infants aged 2-6 months at the Halimah Lubis Midwife Clinic, Deli Serdang Regency in 2022. This type of research is a quasi-experimental study, with a One Group Pretest and Post Test Design approach. The population is all babies aged 2-6 months who are at the Halimah Lubis Midwife Clinic, Deli Serdang Regency in 2022, totaling 36 people. The number of samples used were 36 people obtained by using the total sampling technique. The results obtained in this study were from 36 respondents, there was an effect of baby massage on increasing the weight of babies aged 2-6 months with a value of t = 6.610. There is an effect of baby massage on increasing the weight